Correction: Zhao et al. A Closed-Form Inverse Kinematic Analytical Method for Seven-DOF Space Manipulator with Aspheric Wrist Structure. Machines 2024, 12, 632 - Guojun Zhao; Bo Tao; Du Jiang; Juntong Yun; Hanwen Fan (Machines)
Text Correction [...]